The effect of intellectual capital and financial performance on firm value in manufacturing companies - Jaya, Asrul (Junal Ilmu Manajemen, 2025)
The objective of this research is to analyse the effect of intellectual capital and financial performance on firm value, with the analysis testing multiple linear regression with SPSS Version 26 software. The data utilised in this study are audited financial statements for companies in the manufacturing sector that were listed on the Indonesia Stock Exchange (IDX) during 2020-2023. The study utilised a sample of 72 manufacturing companies listed on the IDX during the 2020-2023 period, employing a purposive sampling technique. The results of the study determined by the t-test output using SPSS show that the intellectual capital variable partially affects the company's value. Partially, financial performance has no significant effect on firm value. The results of the F test show that intellectual capital and financial performance simultaneously have a significant effect on firm value in the manufacturing sector listed on the Indonesia Stock Exchange in 2020-2023.